Heterostructured Au/Pd–M (M = Au, Pd, Pt) nanoparticles with compartmentalized composition, morphology, and electrocatalytic activity. Issue 38 (9th September 2015) - Lutz, Patrick S.; Bae, In-Tae; Maye, Mathew M.
Abstract : The synthesis, processing, and galvanic exchange of three heterostructured nanoparticle systems is described. Abstract : The synthesis, processing, and galvanic exchange of three heterostructured nanoparticle systems is described. The surface accessibility and redox potential of a Au/Pd–Ag dumbbell nanoparticle, where a Au/Pd core/shell region, and a silver region make up the domains, was used to prepare the new nanostructures with controlled composition, morphology, and microstructure. Results indicate that the silver domain was particularly susceptible to galvanic displacement, and was exchanged to Au/Pd–M (M = Au, Pd, Pt). Interestingly, the dumbbell morphology remained after exchange, and the silver region was transformed to hollow, parachute, or concentric domains respectively. The morphology and microstructure change was visualized via TEM and HRTEM, and the composition changes were probed via STEM-EDS imaging and XPS. The electrocatalytic activity of the Au/Pd–M towards methanol oxidation was studied, with results indicating that the Au/Pd–Pt nanoparticles had high activity attributed to the porous nature of the platinum domains.